2019
DOI: 10.1177/0898264319826417
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Social and Material Deprivation for Changes in Health of Older People

Abstract: Objective: We use the panel structure of the Survey of Health, Ageing and Retirement in Europe (SHARE) data for 14 countries to examine the implications of material and social deprivation for health deterioration in old age and mortality. Method: To minimize the potential endogeneity bias, we examine the relationship between deprivation and changes in health rather than levels of health. We include a substantial set of fixed “initial conditions,” and extend the controls with health measures, as observed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
9
1
Order By: Relevance
“…We contribute to this aim by analyzing material and social deprivation separately rather than as a single hardship indicator. 69 This strategy allows us to evaluate their different weight in affecting elderly well-being and to conceive of social policy measures to remove obstacles for healthy aging and to increase individual well-being.…”
Section: Discussionmentioning
confidence: 99%
“…We contribute to this aim by analyzing material and social deprivation separately rather than as a single hardship indicator. 69 This strategy allows us to evaluate their different weight in affecting elderly well-being and to conceive of social policy measures to remove obstacles for healthy aging and to increase individual well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This is done by taking a sample of respondents who did not show any signs of loneliness in wave 5 (see Table 24.1) and examining the role of various factors on the probability of falling into loneliness by wave 6 (see Table 24.2). With this approach -through the differences in loneliness scores between the waves -we account for some of the so called "fixed effects" which might affect both material conditions and loneliness and as a result bias the examined relationship (for another application of this approach see Myck et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Study 1, deprivation was conceptualized at the "administrative area" level, meaning that this indicator was built upon participants' area of residence and aggregated on the basis of several indicators related to the area (Ellaway et al, 2012). In Study 2, deprivation was assessed at an "individual" level, using two self-reported perceived indicators: material deprivation (e.g., having access to necessary groceries, clothes) and social deprivation (e.g., relatedness with people in the local area, vandalism) (Myck et al, 2020).…”
Section: Analyses In Two Large-scale Samplesmentioning
confidence: 99%